Program Edukasi Pasien dan Keluarga terhadap Kepuasan Pasien - Nurhafizah Nurhafizah; Siti Saidah Nasution; Mahnum Lailan Nasution (Jurnal Keperawatan Silampari, 2022)
This study aims to identify how patient and family education programs affect patient satisfaction. This research method is quantitative with a quasi-experimental design using a one-group pretest-posttest approach. The results showed a significant effect between the educational program and patient satisfaction with a value of p = 0.000 (pâ‰¤0.05), where the coefficient of determination showed the magnitude of the effect of the education program on patient satisfaction with an R-value of squared = 0.133. In conclusion, there is a significant effect between educational programs on patient satisfaction on the dimensions of reliability, responsiveness, assurance, empathy, and tangibles with the most dominant influence on the dimensions of reliability. Keywords: Patient Satisfaction, Patient and Family Education Program